Hubungan Antara Transportasi Domain dengan Kualitas Hidup Pasien dengan Gagal Jantung - Denny Maurits Ruku (NUTRIX, 2023)
Quality of life is an important indicator that must receive special attention for patients and health workers and the transportation domain is part of physical activity which is very beneficial for heart failure patients. The aim of this study was to determine the relationship between transportation domains and quality of life in patients with heart failure. Cross-sectional study design was used in this research. Convenience sampling was used in the sampling technique and 180 respondents were included in this research. Pearson correlation, Independent t-test, one-way ANOVAs, and Hierarchical multiple regressions were used to process the data. Transportation domain has a significant relationship with HRQOL of heart failure patients (r= -.20, p< .01), disease-related factors have a significant relationship with HRQOL of heart failure patients such as heart failure medications (r= .17, p< .05), health status (r= .29, p< .01), and NYHA Classification (F= 8.36, p< .001). 3 significant predictor variables for HRQOL; health status (β= 2.43), and NYHA Class III (β= 15.28), and transportation domain (β= -.34). Patients with heart failure have problems in the transport domain, especially in the higher NYHA Class, but improving the transport domain can promise to improve the health status and HRQOL of patients with heart failure. Keywords: Heart failure, Quality of Life, Transport domains. Abstrak Kualitas hidup merupakan salah satu indikator penting yang harus mendapat perhatian khusus bagi pasien serta tenaga kesehatan dan transportasi domain merupakan bagian dari aktifitas fisik yang sangat bermanfaat bagi pasien gagal jantung. Tujuan dari penelitian ini untuk mengetahui hubungan transportasi domain dengan kualitas hidup pada pasien dengan gagal jantung. Cross-sectional study design digunakan dalam penelitian ini. Convenience sampling digunakan dalam Teknik pengambilan sample dan 180 responden diikut sertakan dalam penelitian ini. Pearson correlation, Independent t-test, one-way ANOVAs, dan Hierarchical multiple regressions digunakan untuk mengolah data. Transportasi domain mempunyai hubungan yang signifikan dengan HRQOL dari pasien gagal jantung (r= -.20, p< .01), faktor yang berhubungan dengan penyakit mempunyai hubungan yang signifikan dengan HRQOL pasien gagal jantung seperti, obat gagal jantung (r= .17, p< .05), status kesehatan (r= .29, p< .01), dan NYHA Classification (F= 8.36, p< .001). 3 variable predictor yang signifikan terhadap HRQOL; status kesehatan (β= 2.43), dan NYHA Class III (β= 15.28), dan transportasi domain (β= -.34). Pasien dengan gagal jantung mempunyai masalah dalam transportasi domain terutama pada NYHA Class yang lebih tinggi, namun dengan meningkatkan transportasi domain dapat menjanjikan peningkatan status Kesehatan dan HRQOL dari pasien dengan gagal jantung. Kata Kunci: Gagal jantung, Kualitas Hidup, Transportasi domain.